2016
DOI: 10.1097/tp.0000000000000873
|View full text |Cite
|
Sign up to set email alerts
|

Identification of T Cell–Mediated Vascular Rejection After Kidney Transplantation by the Combined Measurement of 5 Specific MicroRNAs in Blood

Abstract: The combined measurement of miRNA-15B, miRNA-16, miRNA-103A, miRNA-106A, and miRNA-107 may help to better identify TCMVR after renal transplantation in a precise and clinically applicable way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 41 publications
0
34
0
2
Order By: Relevance
“…An additional 6 articles were included into the process after reference review. A total of 29 articles deemed eligible for inclusion were then assessed by the GRADE quality of evidence tool (see Table ), leaving 23 articles in the current systematic review (see Table ), after scoring above the desired threshold. The complete study inclusion process compliant with PRISMA guidelines can be found in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An additional 6 articles were included into the process after reference review. A total of 29 articles deemed eligible for inclusion were then assessed by the GRADE quality of evidence tool (see Table ), leaving 23 articles in the current systematic review (see Table ), after scoring above the desired threshold. The complete study inclusion process compliant with PRISMA guidelines can be found in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also evaluated performances in specific subsets of rejection, including subclinical rejection (SCR), acute cellular rejection (ACR), and antibody mediated rejection (ABMR) . 19 studies examined adult participants (mean age range 44.6‐50.3 from 11 reported studies), 3 examined paediatric patients (mean age range 11.2‐11.9) and 1 examined both (mean age not reported) . Male to female participant ratio was 3:2 amongst 22 studies .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations